Chest X‐rays are less sensitive than multiple breath washout examinations when it comes to detecting early cystic fibrosis lung disease. (24th February 2022) - Svedberg, Marcus; Imberg, Henrik; Gustafsson, Per; Brink, Mela; Caisander, Håkan; Lindblad, Anders
Abstract: Aim: Annual chest X‐ray is recommended as routine surveillance to track cystic fibrosis (CF) lung disease. The aim of this study was to investigate the clinical utility of chest X‐rays to track CF lung disease. Methods: Children at Gothenburg's CF centre who underwent chest X‐rays, multiple breath washouts and chest computed tomography examinations between 1996 and 2016 were included in the study. Chest X‐rays were interpreted with Northern Score (NS). We compared NS to lung clearance index (LCI) and structural lung damage measured by computed tomography using a logistic regression model. Results: A total of 75 children were included over a median period of 13 years (range: 3.0‐18.0 years). The proportion of children with abnormal NS was significantly lower than the proportion of abnormal LCI up to the age of 4 years ( p  < 0.05). A normal NS and a normal LCI at age 6 years were associated with a median (10‐90th percentile) total airway disease of 1.8% (0.4‐4.7%) and bronchiectasis of 0.2% (0.0‐1.5%). Conclusion: Chest X‐rays were less sensitive than multiple breath washout examinations to detect early CF lung disease. The combined results from both methods can be used as an indicator to perform chest computed tomography less frequently.